Religion, Diversity and the Public School: The Challenge for Teacher Education in the Philippines and the U.S. - Milligan, Jeffrey Ayala (Silliman Journal, 2022)
This paper explores the significance of religious diversity and the conflict it often causes for teacher education. It briefly reviews both the U.S. and Philippine experience of the relationship between religion and public education and argues that teacher education in both countries must repond to this challenge by producing teacher who are "prophetic pragmatists".